Effect of chronic use of mobile phone on hearing of young adult age group: a case control study - Prajapati, Viral; Makvana, Bhikhu J.; Gami, Gambhir; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2017)
Background: Exposure to noise from mobile devices is suspected to affect hearing. Objective: To study effect of chronic use of mobile phone on hearing of young adult age group. Methods: The present study is randomized comparative case control study conducted at GMERS Medical College, Dharpur-Patan, North Gujarat, India during March 2014 to August 2015 in which 60 subjects within age group of 15-40 years were included without history of ear disease, ear complains, noise induced trauma to the ear and exposure to noisy environment. After taking written and verbal consent and approval from ethical committee 60 healthy volunteers using the mobile phones infrequently less than 15 minutes a day were included in control group and 60 healthy volunteers using the mobile phones more than 1 hour a day with individual dialogue period more than 30 minutes at a time in a day, for more than 1 year were included in study group. After all the necessary clinical examinations, all subjects were taken in audiometry room for Pure Tone Audiometry in both ears using Pure Tones of 250 Hz- 8000 Hz Frequencies with pure tone audiometry instrument. The collected data were analyzed using SPSS 17 (trial version). Results: The mean age of study group was (26.17 ± 2.65 years) and that of control subjects was (26 ± 3.93 years). The mean usage of mobile phones for study group was 106.0 ± 40.73 minutes and for control group was 9.33 ± 3.65 minutes, the difference was found statistically significant. The mean hearing loss at high frequencies in both ears in study group was 8.47 ± 4.15 dB and in control group was 0.33 ± 1.826 dB that was statistically significant. Out of 30 subjects of study groups, 14 subjects (23.33%) had normal hearing, 32 subjects (53.33%) were having mild high frequency hearing loss and 14 subjects (23.33%) were having moderate high frequency hearing loss. Out of 60 subjects of study groups, 46 subjects (76.67 %) were having high frequency hearing loss (mean hearing loss of 12.17 ± 9.53) in right ear, and 20 subjects (33.33 %) were having high frequency hearing loss (mean hearing loss of 5.16 ±9.143) in left ear. Out of 60 subjects of study groups, 24 subjects (52.17%) with history of tinnitus were having mild to moderate high frequency hearing loss. In 22 subjects (47.82%) with history of warm sensation in the ear were having mild to moderate high frequency hearing loss. In 12 subjects (26.08%) with history of earache were having mild to moderate high frequency hearing loss. Conclusions: There is increase in mean hearing loss (especially at higher frequencies) with increase in duration of daily mobile phone usage. Hearing loss (especially at higher frequencies) is more marked in right ear (mobile phone using ear) as compared to left ear (non-mobile phone using ear). Mobile phone can have a deleterious effect on hearing threshold. Long term use of mobile phone can impair hearing function. Larger, longitudinal studies are needed on mobile phone use and hearing impairment.